Effect of Ag2O Doping on Some Physical Properties of Y156 Superconductor Prepared by Solid State Reaction - Tantivichitvech, Kanchaporn; Sirininlakul, Siri; Bunyoprakan, Warayut; Nilkamjon, Tunyanop; Supadanaison, Rattanasuda; Tiyasri, Somporn; Wongphakdee, Wirat; Udomsamuthirun, Pongkaew (Progress in Applied Science and Technology, 2018)
The influence of Ag2O doping on some properties of Y156 Superconductors (YBa5Cu6O13-y + xAg2O where x = 0, 0.05, 0.10, 0.15, 0.20) prepared by solid state reaction were studied. Yttrium (III)oxide (Y2O3), Barium Carbonate (BaCO3), Copper Oxide (CuO) and Silver(I) Oxide (Ag2O) were used as the precursors. All of samples obtained were investigated by SEM, EDX, resistivity measurement, and the standard iodometric titration. The resistivity measurement by four-point probe technique showed that the highest critical temperature was found in pure Y156 at 95 K. The amount of silver(I) oxide has significant effect to the critical temperature of Y156 superconductor. The highest critical temperature of Y156 doped Ag2O was found in Y156 doped 0.15Ag2O at 93K. However, it had lower critical temperature than Y156 without doping Ag2O. The surface of Y156 doped Ag2O were improved by adding Ag to the porous structure and had narrow grain boundaries. We studied the compositions of elements demonstrated uneven distribution of elements and non-homogeneous material. Also, the results showed that the higher Cu3+/Cu2+ ratio, the higher critical temperature was found.